Users' dissatisfaction with dental care: a population-based household study - Andréa Maria Eleutério de Barros Lima Martins; Raquel Conceição Ferreira; Pedro Eleutério dos Santos Neto; Danilo Lima Carreiro; João Gabriel Silva Souza; Efigênia Ferreira e Ferreira (Universidade de São Paulo, 2015)
OBJECTIVE To examine whether demographic, socioeconomic conditions, oral health subjectivity and characterization of dental care are associated with users' dissatisfaction with such are. METHODS Cross-sectional study of 781 people who required dental care in Montes Claros, MG, Southeastern Brazil, in 2012, a city with of medium-sized population situated in the North of Minas Gerais. Household interviews were conducted to assess the users' dissatisfaction with dental care (dependent variable), demographic, socioeconomic conditions, oral health subjectivity and characterization of dental care (independent variables). Sample calculation was used for the finite population, with estimates made for proportions of dissatisfaction in 50.0% of the population, a 5.0% error margin, a non-response rate of 5.0% and a 2.0% design effect. Logistic regression was used, and the odds ratio was calculated with a 5% significance level and 95% confidence intervals. RESULTS Of the interviewed individuals, 9.0% (7.9%, with correction for design effect) were dissatisfied with the care provided. These were associated with lower educational level; negative self-assessment of oral health; perception that the care provider was unable to give dental care; negative evaluation of the way the patient was treated, the cleanliness of the rooms, based on the examination rooms and the toilets, and the size of the waiting and examination rooms. CONCLUSIONS The rate of dissatisfaction with dental care was low. This dissatisfaction was associated with socioeconomic conditions, subjectivity of oral health, skill of the health professionals relating to the professional-patient relationship and facility infrastructure. Educational interventions are suggested that aim at improving the quality of care among professionals by responsible agencies as is improving the infrastructure of the care units.